Multidirectional research for the therapeutic potential of Phlomoides molucelloides (Bunge) Salmaki: LC-MS/MS, antioxidant, enzyme inhibition, and antiproliferative characteristics - Al Kateeb, Anfal Izaldeen Mutar; Tüfekci, Enis Fuat; Altunoglu, Yasemin Celik; Baloğlu, Mehmet Cengiz; Nilofar, Nilufar; Yıldıztugay, Evren; Jekő, József; Cziáky, Zoltán; Zengin, Gokhan (Elsevier BV, 2024)
Medicinal plants offer natural cures and inspire modern medicine's development. This study examined the antioxidant, enzyme-inhibitory, and antiproliferative activities of various extracts obtained from aerial and root fragments of Phlomoides molucelloides (Bunge) Salmaki. The extracts' overall phenolics, flavonoids, and compounds were defined using colorimetric and LC-MS/MS analyses. The highest total phenolic and flavonoid content was measured in the methanol and infusion extracts of the aerial fragments, with 102.21 mg RE/g and 51.33 mg GAE/g, respectively. Most compounds were defined as flavonoids, predominantly as apigenin and quercetin glycosides. Methanol, 70 % methanol, and infusion extracts from aerial parts had the highest antioxidant activity determined by DPPH, ABTS, CUPRAC, FRAP, metal chelation, and phosphomolybdenum analyses. Moreover, the methanol extract of the roots had the highest anti-acetylcholinesterase, anti-butyrylcholinesterase, and anti-glucosidase activities. The dichloromethane extracts of the roots displayed the highest anti-tyrosinase and anti-amylase activities. The antiproliferative activity of the extracts was investigated against MDA-MB-231, MCF-7, and HeLa cell lines. The lowest IC50 value (875.7 µg/mL) was computed for the methanol extract of the aerial part on the MCF-7 cell line at the 48th h. The findings showed that P. molucelloides extracts may offer a promising therapeutic approach due to their rich bioactive content.